FORMULATION AND EVALUATION OF BUOYANT TABLETS OF KETOCONAZOLE - T., GHOSH; BHARATH, S.; R., NAIK; BASAVARAJ, B.V.; DEVESWARAN, R. (International Journal of Applied Pharmaceutics, 2019)
Objective: The primary objective of the present work was to formulate the gastro-retentive delivery system of ketoconazole (ktz) for its extensive absorption in the stomach. Methods: The solubility and dissolution of antifungal ktz were reported to be higher in the stomach than in the intestinal pH conditions because of its dibasic pKa values 6.51 and 2.94. Thus the development of target buoyant tablets using Hydroxy Propyl Cellulose (HPC) and Xanthan gum (Xg) as polymers along with the effect of citric acid and sodium bicarbonate as an effervescent causing agent of floatation properties and drug release profile was investigated. The formulation optimization was carried out by using a central composite design using Design Expert software by taking HPC, Xanthan gum and sodium bicarbonate as independent variables and floating lag time, in vitro drug release profile as dependent variables respectively. Results: The optimized formulation of ktz buoyant tablets could be developed. The amount of HPC and Xg was found to significantly influence all in vitro response parameters. The results of pre-compression and post-compression parameters of all the formulations were found to be within the standard limits. The optimized formulation exhibited floating lag time of 160 secs with sustained drug release over a period of 12 h in simulated stomach pH condition. Conclusion: Buoyant tablets of ktz with sustained drug release over a period of 12 h in simulated stomach conditions for enhanced drug absorption could be successfully developed.